2019
DOI: 10.1155/2019/1541593
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Resistance and Cardiovascular Risks in Different Groups of Hemodialysis Patients: A Multicenter Study

Abstract: Background. To investigate the association between insulin resistance (IR) and cardiovascular disease (CVD) risks among hemodialysis patients. Methods. We conducted a cross-sectional study between 2013 and 2017, on 384 hemodialysis patients from seven hospital-based-dialysis centers. HOMA-IR is classified according to median value. The CVD risks were defined by the K/DOQI Guidelines. Logistic regression analysis was used. Results. Patients’ age was 60.9 ± 11.8, 58.1% men, and 40.3% overweight/obese. The median… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
(53 reference statements)
0
3
0
1
Order By: Relevance
“…Moreover, the inflammatory reaction toward the dialysis procedure itself, such as dialysis membranes and dialysate fluid, contributes mainly to persistent inflammation. 29,30 On the other hand, we found a significant positive correlation of TSH level and inflammatory markers (hs-CRP and serum ferritin). A similar finding was reported in non-CKD patients by Gupta et al 31 In addition, Valencia and colleagues have reported significantly higher TSH in HD patients with malnutrition, inflammation, and complex syndrome (MICS).…”
Section: Discussionmentioning
confidence: 59%
“…Moreover, the inflammatory reaction toward the dialysis procedure itself, such as dialysis membranes and dialysate fluid, contributes mainly to persistent inflammation. 29,30 On the other hand, we found a significant positive correlation of TSH level and inflammatory markers (hs-CRP and serum ferritin). A similar finding was reported in non-CKD patients by Gupta et al 31 In addition, Valencia and colleagues have reported significantly higher TSH in HD patients with malnutrition, inflammation, and complex syndrome (MICS).…”
Section: Discussionmentioning
confidence: 59%
“…RBP4, a 21-kilodalton protein produced by adipocytes, is also chiefly excreted by the kidney and plays a pivotal role in insulin resistance (IR) 37 . In turn, IR is significantly associated with cardiovascular risk, and can significantly predict cardiovascular disease and mortality in dialysis patients 38 . Additionally, RBP4 is also known to be associated with inflammation and oxidative stress 39 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, diabetes was one of the most common causes of CKD [39,40,43]. On the other hand, insulin resistance was independently associated with cardiovascular risks in ESRD patients [44]. Therefore, there is a consensus that better management of hypertension, and diabetes is required to improve CKD patient care [45][46][47].…”
Section: Discussionmentioning
confidence: 99%